2017
DOI: 10.1136/bmjopen-2017-016236
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to identify and assess the effectiveness of alternatives for people over the age of 65 who are at risk of potentially avoidable hospital admission

Abstract: Background/objectivesThere are some older patients who are ‘at the decision margin’ of admission. This systematic review sought to explore this issue with the following objective: what admission alternatives are there for older patients and are they safe, effective and cost-effective? A secondary objective was to identify the characteristics of those older patients for whom the decision to admit to hospital may be unclear.DesignSystematic review of controlled studies (April 2005–December 2016) with searches in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 34 publications
(40 reference statements)
2
53
0
Order By: Relevance
“…Of the ‘potentially avoidable’ conditions included in this study, COPD had the second highest share of emergency admissions at 15%. However, if other services in the wider care system were available such as a ‘hospital at home’64 or ‘care outreach’ model65 which can respond to patients’ need, it may be possible to avoid such admissions 5 66…”
Section: Discussionmentioning
confidence: 99%
“…Of the ‘potentially avoidable’ conditions included in this study, COPD had the second highest share of emergency admissions at 15%. However, if other services in the wider care system were available such as a ‘hospital at home’64 or ‘care outreach’ model65 which can respond to patients’ need, it may be possible to avoid such admissions 5 66…”
Section: Discussionmentioning
confidence: 99%
“…There is much uncertainty about how best to address the pressing issue of admission avoidance. 97 Our finding that the CRT form of intermediate care can function as a substitution service for brief emergency admissions to hospital for older people is therefore an important one for commissioners. It provides greater confidence that investment in these types of services can indeed reduce secondary care utilisation for a growing and vulnerable population group.…”
Section: Comparative Case Studiesmentioning
confidence: 98%
“…But, in a series of systematic reviews, researchers at Bristol and Cardiff found no consistent evidence that interventions to reduce hospital attendance or admissions succeeded 9. A further systematic review of studies focusing on people over 65 with a predicted high risk of admission also found no compelling evidence 10…”
Section: No Consistent Evidencementioning
confidence: 97%